Study on the Influence of Liquid Nitrogen Cold Soaking on the Temperature Variations and Seepage Characteristics of Coal Samples with Different Moisture Contents. (19th October 2021) - Li, Bo; Zong, Chaohui; Huang, Laisheng; Ren, Yongjie; Lv, Xiaoquan
Abstract : Due to its advantages such as environmental friendliness and remarkable permeability enhancement effect, the technology of liquid nitrogen cold soaking (LNCS) cracking coal has become a hot spot in the research on coal seam permeability enhancement in recent years. The frost heave force generated by water-ice phase transformation and the temperature stress are the main mechanisms of LNCS cracking water-containing coal. This paper focuses on the effect of LNCS on the temperature variations and seepage characteristics of coal. To further this purpose, the temperature measurement test and the permeability test were conducted on coal samples with different moisture contents under LNCS, respectively. In addition, by comparing the computer tomography test results of coal samples before and after LNCS, the internal pore structure changes of coal samples were further analyzed from a three-dimensional perspective. The test results show that the coal sample with a higher moisture content consumes a shorter time to reach internal temperature equilibrium and experiences faster temperature changes. LNCS can enhance coal permeability, and the growth rate of permeability increases exponentially with the increase of moisture content. After the LNCS treatment, the dried coal sample is mainly sprouting new pores on the basis of primary pores; in contrast, for water-containing coal samples, new pores are sprouted while primary pores will penetrate each other spatially to form a fracture network. In the process of LNCS, moisture has a significant effect on the seepage characteristics of coal, so appropriately increasing the moisture content of the coal seam conduces to achieving a better permeability enhancement effect.